2022
DOI: 10.1111/clr.14007
|View full text |Cite
|
Sign up to set email alerts
|

Non‐surgical treatment of mild to moderate peri‐implantitis using an oscillating chitosan brush or a titanium curette—A randomized multicentre controlled clinical trial

Abstract: Objectives: This prospective, parallel-group, examiner-blinded, multicentre, randomized, controlled clinical trial aimed to assess the efficacy of an oscillating chitosan brush (OCB) versus titanium curettes (TC) on clinical parameters in the non-surgical treatment of peri-implantitis. Material and Methods:In five dental specialist clinics, 39 patients with one implant with mild to moderate peri-implantitis, defined as 2-4 mm radiographic reduced bone level, bleeding index (BI) ≥ 2, and probing pocket depth (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…It is demonstrated that disease resolution is unpredictable after non‐surgical peri‐implantitis treatment; thus, novel methods should be developed and tested (Roccuzzo et al, 2020). Non‐surgical treatment of mucositis and peri‐implantitis with OCB compared to TC has been evaluated in clinical studies with equal efficacy for both treatment modalities (Khan et al, 2022; Koldsland & Aass, 2020; Wohlfahrt et al, 2017) The presence of pus was resolved in 19.1% of the implants in the OCB group and with no reduction in the TC group when the treatments were compared in an RCT with a 6‐month follow‐up (2022). Further reduction in the presence of pus following repeated treatments over 12 months was observed in the present study (2022).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is demonstrated that disease resolution is unpredictable after non‐surgical peri‐implantitis treatment; thus, novel methods should be developed and tested (Roccuzzo et al, 2020). Non‐surgical treatment of mucositis and peri‐implantitis with OCB compared to TC has been evaluated in clinical studies with equal efficacy for both treatment modalities (Khan et al, 2022; Koldsland & Aass, 2020; Wohlfahrt et al, 2017) The presence of pus was resolved in 19.1% of the implants in the OCB group and with no reduction in the TC group when the treatments were compared in an RCT with a 6‐month follow‐up (2022). Further reduction in the presence of pus following repeated treatments over 12 months was observed in the present study (2022).…”
Section: Discussionmentioning
confidence: 99%
“…A calibration meeting was held to discuss the study protocol prior to the study start. The detailed clinical protocol and study design have been published (Khan et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations